Exitation of highnumber harmonics by non-relativistic oscillators - Antonov, A.N.; Buts, V.A.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G. (Вопросы атомной науки и техники, 2002)
The results of experimental researches of a possibility of an effective of high numbers harmonics radiation by nonrelativistic oscillators are represented. The good qualitative consent of experimental and theoretical results are obtained. In experiment the millionth harmonic was excited. It is shown, that the investigated mechanism can be used for excitation optical and ultra-violet radiation.